Materials and engineering technology selected, peer reviewed papers from the 2014 International Conference on Materials and Engineering Technology (MET 2014), October 24-26, 2014, Chicago, USA - Liu, Feng (Applied mechanics and materials ;, 2015)
Collection of selected, peer reviewed papers from the 2014 International Conference on Materials and Engineering Technology (MET 2014), October 24-26, 2014, Chicago, USA. The 215 papers are grouped as follows: Chapter 1: Material Science and Material Processing; Chapter 2: Materials and Technologies in Construction Industry; Chapter 3: Researching and Designing of Machines and Mechanisms for the Manufacturing Equipments; Chapter 4: Mechatronics, Automation and Control Engineering; Chapter 5: Embedded System; Chapter 6: Power Electronics and Electrical Engineering; Chapter 7: Communication and Information Technology;Chapter 8: Data, Signal and Image Processing, Applied Computational Technologies; Chapter 9: Engineering Management.